THEMATIC PROGRESSION IN THE STUDENTS’ WRITING RECOUNT TEXT - Johannes Jefria Gultom; Terade M.T Barus (BAHAS, 2020)
AbstractThis study was aimed at investigating the types of theme and the pattern of thematic progression in students’ recount texts. The research was a descriptive qualitative research. It was conducted at SMP Maria Goretti Kabanjahe in North Sumatera. The subjects of the study were 35 students at ninth grade. The data were collected using documentation technique. The procedures of the analysis were: separating a text into clauses, identifying and classifying the types of theme of every clauses, and identifying and classifying the pattern of thematic progression of the texts. There were 310 clauses found in the students’ writing. The findings showed that there are four types of theme in the students’ recount texts, namely: Unmarked Simple Theme (177/57%), Marked Simple Theme (6/2%), Unmarked Multiple Theme (97/31.4%), and Marked Multiple Theme (30/9.6%). In addition, the patterns of thematic progression found were Constant Theme Pattern (47/88%) and Simple Linear Pattern (5/12%). Keyword: Theme and Rheme, Thematic Progression, Recount Text